PERUBAHAN SOSIAL PETANI KARET DI DESA BONGKAL MALANG KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Anggi Pratiwi; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted in The Bongkal Malang Village Of Kelayang Sub-district. The purpose of this research is to analyze the aspects of social change happens on the rubber farmers now compared to the past of The Bongkal Malang Village Of Kelayang Sub-district. This study entitled